(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2022)
The use of fluoroscopy equipment in surgical procedures exposes professionals to ionizing radiation. An important safety aspect is the correct use of personal protective equipment and monitoring of dose levels in workers. In Brazil, the Resolution of the Collegiate Board of Directors (RDC) No. 330/2019 demands the use of individual dosimeter for professionals who exceed the public dose limits. However, when personal dosimeters are not available, the International Atomic Energy Agency (IAEA) recommends attaching a dosimeter to the C-Arm, close to the detector, to estimate the dose received by medical personnel. The objective of this research was to evaluate the levels of exposure in professionals during surgical procedures in the operation room. This analysis was performed by placing OSL dosimeters on the C-arm equipment for eleven months and comparing them with the quantitative values extracted from the equipment in the routine. Two mobile fluoroscopies C-Arm equipment were used in this study. A total of 1231 procedures were evaluated, with a mean dose value of 5.8µSv per procedure. Thus, the maximum number of procedures that the same professional can perform was 140 procedures per day for a staff member considering worker dose limits and 7 procedures per day for staff members using the required protective aprons considering the public dose limits. Although the study shows that the dose limits established by regulatory bodies are above the doses recorded in clinical practice, this situation should not promote false safety in the use of ionizing radiation.